The stars are not yet bells - Assadi, Hannah Lillith (Riverhead Books, 2022)
"A story of secrets, loss, and the betrayals of memory: a lyrical novel of an aging woman confronting her romantic past under the mysterious skies of her island home. Off the coast of Georgia, near Savannah, generations have been tempted by strange blue lights in the sky near an island called Lyra. At the height of WWII, impressionable young Elle Ranier comes to the island when her new husband, Simon, is dispatched by his industrialist father to find the source of the mysterious lights. There they will live for decades, raising a family while employing much of the island's population in a quixotic campaign to find and exploit the elusive minerals rumored to lurk offshore. Fifty years later, as Simon's business is shuttered in disarray, Elle looks back at her life on the mysterious island--and at a secret she herself has guarded for decades. As her memory recedes, her life seems a tangle of questions: How did the business survive so long without ever finding the legendary Lyra stones? How did her own life crumble under treatment for depression? And what became of the other man they brought to the island--handsome, raffish Gabriel, who risked everything to follow the light to its source? With echoes of We Are Not Ourselves and even Jean Rhys's Wide Sargasso Sea, The Stars Are Not Yet Bells is a darkly romantic story of the tantalizing, faithless relationship between ourselves and the lives and souls we leave behind"--